2014
DOI: 10.1136/bmjopen-2013-004320
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal variation of Achilles tendon ruptures in Vancouver, Canada: a retrospective study

Abstract: ObjectiveTo examine the seasonal distribution of tendon ruptures in a large cohort of patients from Vancouver, Canada.DesignRetrospective chart review.SettingAcute Achilles tendon rupture cases that occurred from 1987 to 2010 at an academic hospital in Vancouver, Canada. Information was extracted from an orthopaedic database.ParticipantsNo direct contact was made with the participants. The following information was extracted from the OrthoTrauma database: age, sex, date of injury and season (winter, spring, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 26 publications
3
28
1
Order By: Relevance
“…Most AT ruptures are sport‐related . A significant proportion of ruptures is associated with ball games .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most AT ruptures are sport‐related . A significant proportion of ruptures is associated with ball games .…”
Section: Introductionmentioning
confidence: 99%
“…4 Most AT ruptures are sport-related. 5 A significant proportion of ruptures is associated with ball games. 6 The variation in sport activities might be one reason for the increasing incidence.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that incidence of AT injuries increases dramatically with sport seasons and around 76% of AT injuries studied by Scott et al were sport-related [52]. Hindfoot hypermobility as well as gastroc-soleus incompetence could be a factor in formation of AT tendinopathy among runners based on a biomechanical research study [53].…”
Section: Risk Factors and Patho-etiologymentioning
confidence: 98%
“…Traditionally, middle age group male subjects with irregular sports involvement were considered candidates for AT disorders [50,51]. Neither age nor gender has been proven as a risk factor for AT pathologies [42,52].…”
Section: Risk Factors and Patho-etiologymentioning
confidence: 99%
“…There has been an increased incidence in recent years among both men and women [7] with a peak in the spring that may be due to the increased frequency of adults playing recreational sports [8].…”
Section: Introductionmentioning
confidence: 99%